COVID-19 Vaccinations and the Right to Health in Indonesia - Aziz, Muhammad Rafliansah; Tavares, Muhammad Alfitras; Azhima, Chalisa Jasmine (University of Jember, 2021)
While the COVID-19 pandemic is far from the end, vaccinations have become an inevitable alternative in combating this pandemic. According to the WHO, COVID-19 vaccines are considered public goods. Consequently, they should be distributed equally to the citizens as the fulfillment of the right to health. This study aimed to analyze how COVID-19 vaccinations in Indonesia have been practiced. Also, it examined the government’s responsibility to ensure that COVID-19 vaccines are distributed equally in reflecting distributive justice by enquiring to what extent the government’s policy on independent vaccination relates to the fulfillment of human rights. This study used a legal research method based on a literature review. This study showed that some aspects of the vaccination are under distributive justice and welfare state. However, the Gotong Royong vaccination policy does not refer to distributive justice and the welfare state, resulting in injustice, discrimination, and economic inequality because it only provides certain privileged citizens access to vaccines. Therefore, the government needs to reconsider the Gotong Royong vaccination, focusing on accelerating the vaccination system for vulnerable individuals and groups. KEYWORDS: COVID-19, Right to Health, Social Justice, Vulnerable Groups.